Levetiracetam pharmacokinetics and its covariates: proposal for optimal dosing in the paediatric population - Pokorná, Pavla; Šíma, Martin; Švestková, Natálie; Slanař, Ondřej (European journal of hospital pharmacy, 2023)
OBJECTIVES: Levetiracetam is an anticonvulsive drug increasingly used in paediatric populations. Ontogenesis may alter its pharmacokinetics, demanding dose individualisation of levetiracetam in paediatric populations. We therefore aimed to explore levetiracetam pharmacokinetics and to propose its optimal dosing in the paediatric population. METHODS: Individual levetiracetam pharmacokinetic parameters were calculated based on therapeutic drug monitoring data, using a one-compartmental model, and regression models were used to explore possible covariates. RESULTS: 56 patients aged from 47 days to 18 years were included in the analysis. The median (IQR) volume of distribution and clearance of levetiracetam were 0.7 (0.58-0.85) L/kg and 0.123 (0.085-0.167) L/hour/kg, respectively. Levetiracetam pharmacokinetics were influenced by postnatal age, body size descriptors and renal functional status. CONCLUSIONS: Based on observed relationships, an individualised loading dose of 26.2 mg/kg body weight and maintenance dose of 20.7 mg/mL/min of estimated glomerular filtration rate were calculated as optimal. Since we observed increased levetiracetam clearance in association with valproate co-medication, caution should be used when combining these two drugs.
Keywords: levetiracetam; antikonvulziva; Child; Levetiracetam; pharmacokinetics; dítě; Valproic Acid; Drug Monitoring; drug monitoring; lidé; pediatrics; Humans; drug-related side effects and adverse reactions; monitorování léčiv; kyselina valproová; Anticonvulsants; therapeutic drug monitoring